Piebaldism with repigmentation islands. - Milano, A. (European Journal of Pediatric Dermatology, 2017)
Piebaldism is transmitted in a dominant autosomal way with high penetrance, so in most cases there is an affected parent, although the symptoms can be blurred and go unnoticed; dermatological examination of parents is mandatory in these cases. The pathogenesis of the normopigmented skin islands within the white patches of this disorder is not entirely clear, although their presence is so characteristic to make diagnosis of piebaldism easier. Someone hypothesized that they look like café au lait spots, but the association with NFI (1) has never been demonstrated. It could be photo-induced repigmentation; the hypothesis of photoinduction is based on the absence of such islands at birth, but we also showed in other cases (2) that the hyperpigmented spots form independently of sun exposure. Their color varies from skin colored to dark brown; however a melanocytic pattern was never shown clinically and dermoscopically.